Quality Network for Rational Drug Management - Shankar, P.R.; Upadhyay, D.K. (Journal of Institute of Medicine Nepal, 2007)
The Quality Network for Rational Drug Management (Qu4RaD) is an international collaboration that aims to assist people to improve the use of medicines for health care. The URL is www.qu4rad.net. Journal of Institute of Medicine Vol.28(1) 2006